The Iranians of AUB and Middle Class Formation in the Early Twentieth-Century Middle East. Issue 4 (1st October 2016) - Vejdani, Farzin
Abstract: Iranian graduates of the American University of Beirut (AUB) constitute a neglected cross-section of an emerging middle class in the Middle East. Although the majority of students attending AUB were Arabs from the Ottoman Empire and later post-Ottoman Arab states, there was a notable non-Arab population including Iranians. Many felt an elective affinity with AUB because of the institution's moral educational vision, its proximity to Baha'i leaders in Palestine, and its non-sectarian and practical orientation. Through club activities, published writing and studies, students articulated an understanding of the world that was at once modern and rooted in their religion and culture. By the same token, their career trajectories elucidate the unstable relationship between higher education and employment opportunities. Although they possessed specialized knowledge required for modern professions in government, education, medicine and law, other factors, such as religious discrimination and the lack of strong markets for certain areas of specialization, may have vitiated against the process of professionalization. More broadly, graduates had to navigate the volatile landscape of the post-Ottoman and post-Qajar Middle East in pursuit of their aspirations.